Quantifying the magnitude of the oxygen artefact inherent in culturing airway cells under atmospheric oxygen versus physiological levels. Issue 2 (23rd January 2016) - Kumar, Abhinav; Dailey, Lea Ann; Swedrowska, Magda; Siow, Richard; Mann, Giovanni E.; Vizcay‐Barrena, Gema; Arno, Matthew; Mudway, Ian S.; Forbes, Ben
Abstract : To date, in vitro studies assessing the pulmonary toxicity of inhaled particles have provided poor correlation with in vivo results. We explored whether this discrepancy reflected cellular adaptations in pulmonary cells cultured under atmospheric oxygen concentrations (21%) compared with in vivo alveolar concentrations (100 mm Hg, 13%) and whether this blunted cellular responses to nanoparticle challenge. At 21% oxygen, A549 cells had augmented intracellular glutathione concentrations, with evidence of increased tolerance to CuO nanoparticles, with reduced reactive oxygen species production, blunted transcriptional responses and delayed cell death, compared to cells cultured at 13% oxygen. These data support the contention that standard cell culture conditions pre‐adapt cells to oxidative insults and emphasize the necessity of ensuring normoxic conditions in model systems to improve their predictive value. Abstract :